Penerapan Strategi Talking Stick Pada Siswa SD Untuk Meningkatkan Aktivitas Belajar IPS - Saleh, Sufri (Peneliti.net, 2023)
The aim of this research is to improve social studies activities and learning outcomes through the implementation of the Talking Stick strategy in class V students at State Elementary School 29, Ternate City, academic year 2022/2023. This type of research is Classroom Action Research. The subjects in this research were 32 class V teachers and students. Data collection methods in this research used observation, tests, documentation and interviews. Data analysis techniques in this research include: data collection, data reduction, data presentation, drawing conclusions. The results of this research show that student learning activities have increased from before the action was implemented until the implementation of the second cycle II meeting from 7 students (22%) to 30 students (94%) who expressed opinions. From 7 students (22%) to 26 students (81%) who actively asked questions. From 9 students (28%) to 28 students (87%) who were active in discussions. From 9 students (28%) to 26 students (81%) who listened to the explanation. From 11 students (34%) to 28 students (87%) who answered the question. Meanwhile, judging from the learning outcomes of students whose learning results were completed before the action was implemented, there were 8 students (25%) until the second cycle II meeting was 29 students (91%). The conclusions obtained in this research are as follows: the application of the Talking Stick learning strategy can improve learning activities and learning outcomes in social studies subjects for Class V Students at SD Negeri 29 Ternate City for the 2022/2023 Academic Year.